From Procedural to Dialogical Participation: A Relational Perspective on Participatory Communication in Tourism Village Governance - Oktaviyani, Rena; Hapsari, Dwi Retno; Puspita, Dyah Retna (Fakultas Dakwah UIN Saizu Purwokerto, 2026)
Tourism villages are promoted as a community-based rural development strategy in Indonesia, yet participatory communication practices vary despite similar policy frameworks. This study examines: (1) how individual characteristics influence participatory communication; (2) how media exposure affects participatory communication; and (3) how stakeholders’ roles shape participatory communication in Alamendah and Cibiru Wetan Tourism Villages. Using a post-positivist paradigm and a mixed-methods Sequential Explanatory design, quantitative data from 77 respondents in each village were analyzed using PLS-SEM and complemented with in-depth interviews. he study compares Alamendah Tourism Village, which represents a dialogical–relational governance model characterized by strong local leadership and embedded collective reflection, and Cibiru Wetan Tourism Village, which represents a procedural–operational model marked by institutional integration and centralized coordination. The findings demonstrate that individual characteristics and stakeholders’ roles significantly influence participatory communication in Alamendah but not in Cibiru Wetan, while media exposure shows no significant effect in either case. The results indicate that participatory communication is determined less by structural strength or media intensity and more by how communicative authority and dialogical spaces are distributed and institutionalized in governance practices. Conceptually, the study highlights a relational understanding of participatory communication, emphasizing dialogical space and institutionalized reflection as core determinants of participatory depth.